2022
DOI: 10.1186/s12913-022-08284-9
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness and management during the first phase of the COVID-19 outbreak - a survey among emergency primary care services in Norway

Abstract: Background The emergency primary care (EPC) services in Norway have been at the frontline of the COVID-19 pandemic. Knowledge about the EPC services’ management of the COVID-19 outbreak can be used to prepare for future outbreaks and improve patient management. The objectives of this study were to identify pandemic preparedness and management strategies in EPC centres in Norway during the COVID-19 outbreak. Methods Questions regarding patient manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
(43 reference statements)
1
4
0
Order By: Relevance
“…The document review revealed that national and municipality preparedness plans were outdated and failed to account for a long-term pandemic with such a cross-sectoral impact. This finding is consistent with reports from the early phase on the pandemic, both from Norway [ 2 , 9 , 45 ] and abroad [ 46 ]. By constantly revising guidelines and procedures for their local health system, and by disseminating information and training staff in new procedures, managers improved their understanding of current practice and enforcement.…”
Section: Discussionsupporting
confidence: 93%
“…The document review revealed that national and municipality preparedness plans were outdated and failed to account for a long-term pandemic with such a cross-sectoral impact. This finding is consistent with reports from the early phase on the pandemic, both from Norway [ 2 , 9 , 45 ] and abroad [ 46 ]. By constantly revising guidelines and procedures for their local health system, and by disseminating information and training staff in new procedures, managers improved their understanding of current practice and enforcement.…”
Section: Discussionsupporting
confidence: 93%
“…When asked about agreements to increase surge capacity with staff not normally employed at the EPHCC, 39,1% replied to have made such arrangements with other health actors in their district. This is also in-line with findings from Dale et al, where 44.6% of the staff that contributed during the initial phase of the Covid-19 pandemic at Norwegian EPHCCs were other personnel than those employed at the EPHCC [48].…”
Section: Discussionsupporting
confidence: 91%
“…When physical attendance is difficult, a change to phone contact is logical, and this has also been found in studies from other parts of the health care sector. 27 Therefore, it might be useful, looking forward, to have a plan for increasing the number of phone lines to the crisis shelters, and to have more staff available to operate the phones. A qualitative study from Sweden mentions these kinds of challenges for social work professionals at women’s crisis shelters.…”
Section: Discussionmentioning
confidence: 99%